Rossiia. Federal'noe sobranie 94 . Rossiia. Federal'noe sobranie 94 . Russia. Federal Assembly '94 . Россия. Федеральное собрание 94 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Promotional video by the political bloc "Rossiiskoe dvizheniie demokraticheskikh reform" ("Russian Movement of Democratic Reforms"); interview with a representative of the "Iavlinskii-Boldyrev-Lukin" bloc; presentation by the "Vybor Rossii" (Russia's Choice) bloc. Featured in the program: Gaidar, Egor Timurovich (First Deputy Prime Minister of the Russian Federation); Gazmanov, Oleg Mikhailovich (Singer); Pamfilova, Ella Aleksandrovna (Minister of Social Welfare of the Russian Population); Makarevich, Andrei Vadimovich (Musician); Zhvanetskii, Mikhail Mikhailovich (Writer); Malikov, Dmitrii IUr'evich (Singer) Показ агитационного ролика блока "Российское движение демократических реформ"; беседа с представителем блока "Явлинский-Болдырев-Лукин"; выступление представителей блока "Выбор России.". В программе участвуют: Гайдар, Егор Тимурович (Первый заместитель председателя Правительства Российской Федерации); Газманов, Олег Михайлович (Певец); Памфилова, Элла Александровна (Министр социальной защиты населения России); Макаревич, Андрей Вадимович (Музыкант); Жванецкий, Михаил Михайлович (Писатель); Маликов, Дмитрий Юрьевич (Певец)